2020
DOI: 10.21037/hbsn.2019.04.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative long-term outcomes for pancreatic volume change, nutritional status, and incidence of new-onset diabetes between pancreatogastrostomy and pancreatojejunostomy after pancreaticoduodenectomy

Abstract: Background: The difference in volume change in a pancreatic remnant according to the type of pancreaticoenterostomy after pancreaticoduodenectomy (PD) for long-term follow-up is unknown. Also, there are few studies that evaluate the difference in general nutritional status and pancreatic endocrine function, including new-onset diabetes mellitus (NODM) depending on the type of pancreaticoenterostomy.This study aimed to compare serial pancreatic volume changes in pancreatic remnants between pancreatogastrostomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…Several clinical studies have examined the incidence of diabetes after PD, and the incidence rates for these studies are reported as 10% to 30% ( 10 , 14–18 ). In this study, the incidence of diabetes was 53.8% at 36 months postoperatively, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical studies have examined the incidence of diabetes after PD, and the incidence rates for these studies are reported as 10% to 30% ( 10 , 14–18 ). In this study, the incidence of diabetes was 53.8% at 36 months postoperatively, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason may be due to differences in the way diabetes was diagnosed. We used the 75-g OGTT, HbA1c, and FBG to diagnose diabetes; however, almost all reported studies have used only HbA1c and FBG ( 10 , 14–17 ). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] However again, reports have been conflicting; other studies have concluded that pancreatogastrostomy and pancreatojejunostomy following pancreatoduodenectomy induced a similar reduction of pancreatic volume, and made no difference to general nutritional status or the incidence of new-onset diabetes mellitus (NODM). 32 No single technical variation of the pancreaticojejunal or pancreaticogastric anastomosis has been found consistently to be superior to another. However, pancreatojejunostomy may lead to a more preferable physiological structure.…”
Section: Discussionmentioning
confidence: 99%
“…При этом частота стеатореи достоверно не отличалась. Также не отмечено различий в уровне сывороточного альбумина и индексе массы тела (ИМТ) [42].…”
Section: экзокринная недостаточность поджелудочной железыunclassified